2022
DOI: 10.12998/wjcc.v10.i29.10600
|View full text |Cite
|
Sign up to set email alerts
|

Serratia fonticola and its role as a single pathogen causing emphysematous pyelonephritis in a non-diabetic patient: A case report

Abstract: BACKGROUND Diagnosis of emphysematous pyelonephritis has been described around the world for some decades, frequently associated with Escherichia coli and other anaerobic, gas-forming bacteria and mostly in patients living with diabetes. We present a case report of emphysematous pyelonephritis in a non-diabetic patient caused by Serratia fonticola as well as a brief literature review to draw attention to this rare pathogen as a cause of pyelone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…However, only one case (case 2) survived, while cases 3 and 4 resulted in fatalities. Other studies by Villasuso-Alcocer et al and Mahajan et al have shown successful outcomes using treatments other than ceftriaxone despite invasive interventions such as surgical removal of a cerebellar abscess and combined endoscopic intrarenal surgery, respectively [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, only one case (case 2) survived, while cases 3 and 4 resulted in fatalities. Other studies by Villasuso-Alcocer et al and Mahajan et al have shown successful outcomes using treatments other than ceftriaxone despite invasive interventions such as surgical removal of a cerebellar abscess and combined endoscopic intrarenal surgery, respectively [ 6 , 11 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is linked to the presence of a FOMA-type and an inducible chromosomal β-lactamase AmpC in Serratia. These not only confer antibiotic resistance but also facilitate the transmission of antimicrobial resistance elements to other bacteria, increasing the risk of rapid development into polymicrobial bacteremia or septicemia [6]. Earlier, Gorret et al reported a patient treated empirically with gentamicin and cloxacillin, later shifting to ciprofloxacin and ceftriaxone after surgery [10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation